Feasibility of producing wood fibre-reinforced geopolymer composites (WFRGC) - Mohd Mustafa Al Bakri, Abdullah; Mohd Izzat, Ahmad; Muhammad Faheem, Mohd Tahir; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr.; Khairul Nizar, Ismail, Assoc. Prof. Dr.; Mohamed, Bnhussain, Prof. Dr.; Rafiza, Abdul Razak; Zarina, Yahya; Liyana, Jamaludin (Trans Tech Publications, 2013)
Link to publisher's homepage at http://www.ttp.net/